رأس المال الاجتماعي كقوة محركة للمنظمات - هشام, معيري; حسان, الجيلاني (Sciences de l'Homme et de la Société, 2017)
إن مفهوم رأس المال الاجتماعي من المفاهيم الخلافية، فقد استخدم في العديد من المجالات العلمية، مثل المجال السياسي، الاقتصادي، الاجتماعي، وكان هذا المفهوم مقرون بالقضايا التي تثيرها هذه المجالات العلمية.غير أن انتشار هذا المفهوم في السيا التظييمي كان مقرونا بالانتشار المتاايد للأبحاث في شبكات العلاقات الاجتماعية القائمة داخل المظيمات. فمفهوم رأس المال الاجتماعي يعبر عن أهمية العلاقات الاجتماعية داخل المظيمة، ويؤكد على أن طبيعة هذه العلاقات والمعايير الحاكمة لها تمثل صورة من صور رأس المال لا يقل أهمية عن رؤوس الأموال الأخرى داخل المظيمة. ومحاولتظا هظا جاءت لفهم رأس المال الاجتماعي في السيا التظييمي، من خلال تحديد أبعاده المختلفة، وكذا تحديد الماايا التي تستفيد مظها المظيمة جراء تطوير هذا الظوع من رأس المال. Abstract: The concept of social capital is controversial. It has been used in many scientific fields, such as politics, economics, and social sciences. It was coupled issues raised by these scientific fields. However, the spread of this concept in the organizational context was linked with the growing proliferation of research in the networks of social relations that exist within organizations. The concept of social capital reflects the importance of social relationships within the organization. It emphasizes that the nature of these relationships and the criteria governing them represent an image of the capital that is as important as other capital within the organization. Here was our attempt to understand the social capital in the organizational context, by selecting its different dimensions, as well as to identify its advantages that the organization benefits from it as a result of developing this type of capital.